Malnutrition Factors among Children Under Five with Social, Economic, and Public Health Impacts in Resource-Limited Contexts: A Scoping Review - Rizky Saputri, Andini; Ari Nugroho, Fajar; Nila K, Fuadiyah (Indonesian Journal of Human Nutrition, 2026)
Malnutrition remains a major public health concern, particularly among children in resource-limited settings. Multiple factors influence its occurrence, including socioeconomic status, environmental conditions, immunization coverage, infections, and the effectiveness of nutrition interventions. This study aims to examine the key determinants of malnutrition among children under five years of age in low- and middle-income countries and to identify evidence-based strategies to reduce its impact. This scoping review followed the Arksey and O’Malley framework and adhered to the PRISMA-ScR guidelines. A comprehensive search of the PubMed database was conducted for articles published between 2022 and 2023. Titles and abstracts were screened, followed by full-text assessment using predefined inclusion and exclusion criteria. Data from eligible studies were charted and analyzed using a descriptive thematic approach to identify determinants of malnutrition and related interventions. A total of 891 articles were identified, and nine studies met the eligibility criteria. Most included studies used observational designs and were conducted in low- and middle-income settings among children under five. The findings show that low socioeconomic status increases the risk of malnutrition due to limited access to nutritious food and healthcare services. Poor sanitation and inadequate immunization were also associated with higher malnutrition risk through increased susceptibility to infectious diseases. Recurrent infections further sustain the cycle of malnutrition and immune dysfunction. The evidence indicates that interventions such as behavior change communication (BCC), micronutrient supplementation, improved protein intake, and integrated WaSH programs can reduce malnutrition. Addressing malnutrition requires a comprehensive and multi-sectoral approach that integrates economic support, healthcare access, improved sanitation, and sustainable food security strategies to improve child health outcomes.